Reading between the lines : - McRae, John (Cambridge Univ. Press, 1995)
The book is organised thematically, covering such topics as family, Environment, Rebellion, and Women. There is a minimum of three texts in each unit and the related activities are varied and thought-provoking, to simulate and sustain discussion